Physicochemical Properties Of Four Selected Food Spices Of Nigerian Origin: Alligator Pepper, Black Pepper, Ginger And Cloves - Okunade, A.F.; Agboola, T.I.; Ogunsina, B.S.; Salau, A.O.; Salami, A. (Ife Journal of Technology, 2019)
Spices are largely used to enhance the physical, sensory and textural characteristics of foods being very beneficial to human health. Some physicochemical properties of alligator pepper, black pepper, ginger and cloves were investigated, following standard procedures. It was found that water and oil absorption capacity of the spices flour samples were in the range of 127.47-178.68 g of water per 100 g of flour and 106.66-219.18 g of oil per 100 g of flour, while angle of repose, tap bulk density, loose bulk density were in the range of 45.16-50.53o, 0.10-0.59 gcm3, 0.07- 0.44 gcm3, respectively. For each of the sieve mesh sizes considered, the flour samples indicated significantly different (p<0.05) particle sizes. The fat, crude fibre, ash and protein contents of the spices ranged from 4.17-7.5, 2.31-18.19, 2.84-5.7 and 1.91-13.01 g/100g of dry matter, respectively. Phytochemical screening shows that the spices contain alkaloids, flavonoids, phenols, tannins and saponins in the range of 8.81-51.60%, 4.45-7.54 mg GAE/g, 23.47-41.73 mg GAE/g, 0.68-2.66 mg TAE/100 g and 1.16- 6.07 mg/100 g, respectively. These data find relevance in industrial processing of these spices into value added products and promises a boost in income obtainable from spices value chain.